Analisis Upaya Petani dalam Meningkatkan Produktivitas Kelapa Sawit Berdasarkan Perspektif Bisnis Syariah di Nagari Kamang Baru - Anggraini, Fadilla; Imamuddin, M.; Miswardi, Miswardi; Fauzan, Rusydi (Lembaga Yasin AlSys, 2026)
Oil palm productivity has received attention in various studies, yet studies specifically discussing independent smallholders’ efforts to increase oil palm productivity from the perspective of sharia business remain limited. This study aims to analyze oil palm farmers’ efforts to increase productivity, identify the obstacles they face, and analyze farmers’ strategies for overcoming these obstacles based on the perspective of sharia business in Nagari Kamang Baru. This study used a qualitative approach with a case study design, involving independent oil palm farmers and farm laborers selected through purposive sampling. Data were collected through in-depth interviews, field observations, and documentation, then analyzed using the interactive analysis model of Miles, Huberman, and Saldaña through the stages of data reduction, data presentation, and conclusion drawing. The results show that efforts to increase productivity were carried out through land fertilization before planting, the use of superior seedlings, regular fertilization, plantation maintenance, and oil palm replanting. The main obstacles faced by farmers included environmental factors, seedling quality, labor availability, limited capital, and farm business management. In addition, cooperative practices among farmers, mutual assistance in the harvesting process, and efforts to maintain the sustainability of farm businesses reflect the application of sharia business values in oil palm agricultural management. This study contributes to the development of sharia agribusiness studies and expands understanding of the relationship between agricultural productivity and the application of sharia business principles in oil palm farm management. The implications of this study emphasize the importance of strengthening farmers’ capacity, sharia value-based cooperation, and sustainable farm business governance in increasing oil palm productivity.